Examining the Influence of Bitcoin Market Cycles on Earnings Reporting Behavior in Firms with Cryptocurrency Exposure - Joshlyn Tungarang; Kevin Deniswara (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2026)
Purpose: This study examines whether stages of the Bitcoin market cycle are associated with discretionary accruals of U.S.-listed companies with measurable exposure to Bitcoin. We aim to address a gap in the crypto-accounting literature, as the prior literature has concentrated on disclosure quality, fair value measurement, and audit risk, but not on accrual-based earnings management behavior in different market conditions. Method: Discretionary accruals are measured with Modified Jones Model and estimates are analyzed with Linear Mixed Models with an AR(1) repeated covariance structure to address severe serial autocorrelation. The data are an unbalanced panel of 10 firms and 162 firm-quarter observations from Q1 2020 to Q4 2025. Findings: Within this sample, discretionary accruals yield no statistically significant association with Bitcoin market cycle phase, cryptocurrency exposure intensity, and the interaction between both of them. Only profitability has proved to be relevant. This could indicate that reporting incentives in this firm category are also driven by traditional profitability dynamics, rather than crypto market sentiment. These findings can be explained by rational expectations theory and the political cost hypothesis. Results may suggest that the combination of ASU 2023-08’s fair value standard, audit oversight, and governance structures limits market-driven accrual manipulation among early-adopting firms. Implications: For investors and analysts, the emphasis on profitability metrics over Bitcoin cycle conditions as a reporting signal has practical implications for how cryptocurrency-exposed companies are evaluated. For standard setters in jurisdictions where accounting standards for cryptocurrencies are still being developed, this research gives insight on whether fair value standards and market sentiment acts as behavioral constraint. Novelty/Value: This study provides the first longitudinal, firm-level empirical test of Bitcoin market cycle effects on earnings management, contributing to emerging literature on institutional constraints in crypto-reporting environments.